1979
DOI: 10.1002/jsfa.2740300404
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of potato crude protein as influenced by manuring and amino acid composition

Abstract: Potatoes were grown in pots and fertilised with varying amounts of nitrogen (as nitrate or ammonium sulphate or urea), phosphorus, potassium and cow manure. The largest yield, 451 g D M per pot, was obtained with nitrogen in the form of urea. N-applications and P-and K-deficiency in the soil increased the total-N content, which varied from 1.14-3.07%. Concentrations of nitrate-N (0.001-0.016 %) were negligible. Increasing N-concentrations were associated with decreases in the crude protein of most amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…With a yield of 8788 kg per hectare, production of 0.62 kg maize in Germany required 0.71 m 2 year. This Case-specific data were used (see Table 3) c Source: (Gilani et al 2005), except for potatoes (white (Kies and Fox 1972;Eppendorfer et al 1979;Khan et al 1992;Gahlawat and Sehgal 1998), sweet (Ravindran et al 1995)) 0.71 m 2 year could have been used directly to produce human food crops and could yield maximally 0.049 kg HDP ((7019 kg wheat per ha×0.904 DM per kg wheat×125.1 g protein per kg DM wheat × 87 % digestibility / 10,000) × 0.71 m 2 year). In total, the land used to produce 1 kg of eggs and associated chicken meat could have yielded directly 0.27 kg of HDP from human food crops.…”
Section: Results Of Land Use Ratio (Protein Perspective)mentioning
confidence: 99%
“…With a yield of 8788 kg per hectare, production of 0.62 kg maize in Germany required 0.71 m 2 year. This Case-specific data were used (see Table 3) c Source: (Gilani et al 2005), except for potatoes (white (Kies and Fox 1972;Eppendorfer et al 1979;Khan et al 1992;Gahlawat and Sehgal 1998), sweet (Ravindran et al 1995)) 0.71 m 2 year could have been used directly to produce human food crops and could yield maximally 0.049 kg HDP ((7019 kg wheat per ha×0.904 DM per kg wheat×125.1 g protein per kg DM wheat × 87 % digestibility / 10,000) × 0.71 m 2 year). In total, the land used to produce 1 kg of eggs and associated chicken meat could have yielded directly 0.27 kg of HDP from human food crops.…”
Section: Results Of Land Use Ratio (Protein Perspective)mentioning
confidence: 99%
“…Eppendorfer, Eggum, and Bille (1979) reported that the dry-matter content of potato was directly proportional to the amount of N applied to the soil, and this increase was associated with the protein content (Srikumar and Ockerman 1990). Tuber dry-matter contents at 495 and 660 Kg N ha -1 obtained the greatest values (14% and 22%, respectively) in the first and second growing periods, respectively.…”
Section: Dry-matter Concentrationmentioning
confidence: 94%
“…Plant proteins and non-protein N-fractions also contain non-essential amino acids, the amounts of which have a bearing on the protein quality of plants (FAO/WHO 1973). In earlier studies of effects of nutrient supply on amino acid composition and protein quality of vegetables (Eppendorfer 1978;Eppendorfer et al 1979) only results of total amino acids analyses were published. However, for a more detailed understanding of nutrient effects on variations of nitrogen fractions in plants, free amino acids, amides and nitrate have also to be considered.…”
Section: Introductionmentioning
confidence: 99%